Measuring the Effectiveness of Zakat Disbursement at Amil Zakat Institution Dewan Da’wah Utilizing Zakat Core Principle Approach - Efri Syamsul Bahri; Ade Salamun; Zainal Arif (Prodi Perbankan Syariah FAI UMT, 2022)
Zakat accumulation inside Indonesia has shown significant growth, with an average of 25.71% in the previous five years (2015-2019). Zakat collection contributions came from Baznas, Baznas Province, Baznas Regency/City, including Amil Zakat Entity (LAZ), with the most significant contribution of LAZ reaching 56.79%. The LAZ Dewan Da’wah is one LAZ contributing to realising the zakat governance objectives. This study desires to measure the effectiveness of allocating Zakat, Infaq/Alms, and other religious, social funds at LAZ Dewan Da’wah. The effectiveness’ level was measured utilising the zakat core principle model in the allocation to collection ratio (ACR) directions. The research object used the LAZ Dewan Da’wah financial statements from 2015 to 2019. The results presentation, the allocation effectiveness at LAZ Dewan Da’wah for 2015-2019 reached 92% in the High-Effective type with an ACR value of ≥ 90 per cent. It displays that the LAZ Dewan Da’wah is on track. Thus, LAZ Dewan Da’wah has contributed to achieving the national zakat governance goals, namely, increasing zakat’s benefits to realise the welfare of mustahiq, including poverty alleviation